Operaie in casa, Operaie in fabbrica - Maurizia Morini (Laboratoire Italien)
During the 1970s, the features of Italian feminism tended to vary greatly from one city to another, reflecting the differences between the social, political and cultural histories of the different regions. We like to talk about plural “feminisms” because very different groups sprang up within the feminist movement. These groups documented their existence through the publication of magazines, sometimes produced in single issues. Common themes included health, knowledge of one’s own body, contraception, abortion, social services. Other themes highlighted differences between groups: emancipation/liberation, specificity/equality, wages for domestic work, paid work. In Emilia, a region where women achieved emancipation and were able to work, the groups that campaigned for a domestic wage had a short and limited life, but it was amid the realities of Padua and Naples that women were most strongly and lastingly committed to the campaign for domestic wages. This commented portfolio illustrates this struggle and these differences.